LITERACIES, EVENTS AND SOCIAL PRACTICES - Magalhães, Izabel; França, Lucimar; Fernando Fidelix Nunes (Cadernos de Linguagem e Sociedade, 2023)
The social practices of literacy have been the focus of investigators in the fields of Linguistics and Anthropology since the early 1980s. The works of Heath (1983) and Street (1984) are seminal in the development of this trend of studies, having influenced a great number of scholars, both linguists and anthropologists, interested in the relation between language and society.